The mechanism and control of Jagged1 expression in Sertoli cells - Ryu Okada; Taro Hara; Tomomi Sato; Nobuhiko Kojima; Yukio Nishina (Regenerative Therapy, 2016)
The regulation of Sertoli cells by some hormones and signaling factors is important for normal spermatogenesis. Notch signaling is considered to be necessary for normal spermatogenesis in mouse. In this study, we revealed two new facts about Sertoli cells by western blotting experiments on different types of primary cells and microdissected tubules. The first is that Sertoli cells express the Jagged1 ligand in mice testes. The second is that the expression level of Jagged1 oscillates in the seminiferous epithelial cycle. Therefore, we inferred that Jagged1 in Sertoli cells contributes to the Notch signaling involved in spermatogenesis. Furthermore, we examined the regulation of Jagged1 expression and found that Jagged1 expression was suppressed by cAMP signaling and was promoted by TNF-α signaling in Sertoli cells. When cAMP and TNF-α were simultaneously added to Sertoli cells, Jagged1 expression was suppressed. Therefore, cAMP signaling dominates Jagged1 expression over TNF-α signaling. These results suggest that cAMP signaling may cause the periodicity of Jagged1 expression in the seminiferous epithelial cycle, and controlling Jagged1 expression by adding TNF-α or cAMP may contribute to normal spermatogenesis in vitro.